1998
DOI: 10.1508/cytologia.63.365
|View full text |Cite
|
Sign up to set email alerts
|

A C-band Polymorphism of the X Chromosome in Akodon azarae (Rodentia, Cricetidae).

Abstract: Akodon azarae is one of several rodent species in whose populations XY fully fertile females are found. The chromosomes of 83 specimens (40 females, 43 males) from three localities were studied. A high incidence of XY females was observed: 21 of the females presented an XY karyotype. The X chromosome relative length corresponded to 8.2% of the genome, but a significative portion of it consisted of C-positive material, giving to the euchromatic part a relative length of 5.07%, in agreement with the estimated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
4
14
0
Order By: Relevance
“…In accordance with previous descriptions (Bianchi et al 1971, Ortiz et al 1998, the specimens of A. azarae showed a karyotype composed of 17 telocentric autosome pairs, a small bibrachial one which is characteristic of the genus, a subterminal X and a bibrachial Y that is the smallest chromosome of the karyotype. Only the first pair, the small bibrachial and the sex chromosomes are recognizable in unbanded cells.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with previous descriptions (Bianchi et al 1971, Ortiz et al 1998, the specimens of A. azarae showed a karyotype composed of 17 telocentric autosome pairs, a small bibrachial one which is characteristic of the genus, a subterminal X and a bibrachial Y that is the smallest chromosome of the karyotype. Only the first pair, the small bibrachial and the sex chromosomes are recognizable in unbanded cells.…”
Section: Resultssupporting
confidence: 89%
“…Again, only the first pair, the small bibraquial and the gonosomes can be identified in unbanded metaphases. With respect to C-bands, it has been shown that in A. azarae, centromeric bands can be found in the autosomes, excepting the small biarmed one; the Y chromo- some is heterochromatic, and the X presents several bands that originate a polymorphic pattern (Ortiz et al 1998). In A. boliviensis, on the other hand, the only heterochromatic regions observed are the short arm of the X chromosome and the long arm of the Y (Pinna Senn et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the taxonomy and systematics of the genus remain unresolved, mainly due to the great similarity between its species, and thus a comprehensive revision of the genus would be welcome (Diaz et al 1999). This genus is cytogenetically very interesting because of its systematic complexity, its considerable karyotypic diversity (2n =10-52), but, paradoxically, karyotypically indistinguishable species, the existence of intraspecific variation affecting the autosomes and the sex chromosomes, and the presence of species with fertile XY-females (Bianchi et al 1971, 1973, 1979a, b, 1989, 1993, Fagundes et al 1998, Fernandez-Donoso et al 2001, Gallardo 1982, Ortiz et al 1998, Silva and Yonenaga-Yassuda 1998, Vitullo et al 1986, Wittouck et al 1995.…”
mentioning
confidence: 99%
“…azarae is one of the species of Akodon in whose populations fertile XY females are present (Bianchi and Contreras 1967, Bianchi et al 1971, 1989, 1993, Espinosa and Vitullo 1996, Ortiz et al 1998, Solari et al 1989. A. molinae and A. dolores share an interesting polymorphism of their first chromosome pair, which can appear as a submetacentric or as 2 subterminal chromosomes, whilst A. dolores exclusively shows Robertsonian polymorphisms of pairs 2 to 5 (Bianchi et al 1973, 1979a, b, Fernandez-Donoso et al 2001, Wittouck et al 1995.…”
mentioning
confidence: 99%